A cross-sectional study on determinants of immunization coverage in urban area Chidambaram, Tamil Nadu - Priya, D. P. Lakshmi; Kalyani, P.; Bala, B. Sindhu (International Journal Of Community Medicine And Public Health, 2021)
Background: Immunization is one of the cost effective measures preventing approximately 2 to 3 million deaths in young children every year. Inspite of the progress in vaccination coverage challenges still remain for underserved and inaccessible children. It is therefore essential to evaluate the immunization coverage at periodic intervals and improve coverage in vulnerable areas. Methods: A cross-sectional study was conducted among 152 children aged 12 to 42 months in urban Chidambaram from September to October 2018. We collected details regarding immunization from vaccination card or mother’s recall. A pretested semi-structured proforma was used to collect sociodemographic variables. Data were collected, compiled and tabulated using microsoft excel and analyzed using SPSS 20.0 version. Results: Complete immunization coverage was 80.3% and 19.7% were partially immunized. Lack of awareness is the major reason for failure of full immunization (63.3%). Immunization coverage was higher when parents studied up to higher secondary or graduates (mother 91.3%, father 87.5%, p value 0.01), father do skilled jobs (91.9%, p value 0.02), among first birth ordered children (88.3%, p value 0.01), children born in healthcare facility and among mothers who received antenatal care during pregnancy (80.8% each, p value 0.04). Conclusions: Lack of awareness, parents’ literacy and occupation, place of birth, antenatal services and number of children in the family are important determinants of immunisation coverage. Apart from strengthening of infrastructure for better delivery of mother and child health services other issues also need to be addressed for better immunization practices.